Tie Strength Analysis: New Metrics and Open Problems - Brandão, Michele A.; Moro, Mirella M. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2017)
The study of social ties has lead to building rigorous models that reveal the evolution of social networks and their dynamism. In this context, a central aspect is the strength of ties, which allows the study of the roles of relationships. Here, besides analyzing the strength of co-authorship ties, we also present a set of metrics and algorithms to measure such strength.